Malaysian Industrial Collaborations for Skills Development in 4th Industrial Revolution - Sohimi, Nurul Eizzaty; Mohd Affandi, Haryanti; Rasul, Mohd Sattar; Mohd Yasin, Ruhizan; Nordin, Norazah; Adam, Sariyah (Journal of Technical Education and Training, 2019)
The fourth industrial revolution (4IR) is a new revolution with a combination of communication, IT data and physical system, also known as a cyber-physical system. The arrival of 4IR in Malaysian needs collaboration from industry player and institutions in developing the skills that merge in 4IR because through this collaboration the competency of the workforces can be increased. This study is conducted to identify the strategic plan that can use as a guideline by Department of Skills Development in collaboration with the industry and institutions for skills development in 4IR. A qualitative survey research design within a focus group was adopted in this study. The focus group discussion has been done involving members of the Department of Skills Development Malaysia, an academician from the different institutions in Malaysia and industrial players from a various industry in Malaysia. The findings show ten strategic plan that can be used as a guideline by the Department of Skills Development in order to develop a skill for 4IR which are designing assessment of industrial training with employers, strengthens industry involvement in curriculum development, identify industries that have the interest/needs of the institutions and create industry requirements for the institutions. Next, the education and training provider must be open and create platform to accept industry opinions, appoint suitable experts from 4IR industries for NOSS development, penetrate international standard (dual certification) and emphasis industry collaboration with training providers to employed workers. Moreover, industry and institutions have to collaborate to sharing resources (skills, knowledge, facilities and funding), reskilling and upskilling workers using train the trainer approach collaborate with industry expert and lastly is collaboration or partnership with industry.